Leveraging agricultural interventions for improving nutrition in Egypt - El-Enbaby, Hoda; Ecker, Olivier; Figueroa, Jose Luis; Leroy, Jef L.; Breisinger, Clemens (International Food Policy Research Institute, 2019)
The success of nutrition-sensitive agricultural interventions in countries in the Middle East and North Africa has not been examined in much depth. To narrow this knowledge gap, a smallholder farm household survey was conducted in six governorates in Upper Egypt in April and May 2018 following the winter cropping season. The survey provides comprehensive information on agriculture, nutrition, and health. Specifically, the study sought to identify potential levers and challenges along the agriculture-nutrition impact pathways, with attention to value chain development approaches for promoting horticulture. This policy note presents findings from the survey. It should be useful in the design and implementation of nutrition-sensitive agricultural programs in Upper Egypt.